Cutting-edge developments in the application of hydrogels for treating skin photoaging - Cao, Lili; Qian, Xiaoying; Min, Jie; Zhang, Zhongfeng; Yu, Meiping; Yuan, Dan (Frontiers in Materials, 2024)
Skin photoaging, caused by prolonged exposure to ultraviolet (UV) radiation, manifests as intricate biological transformations, encompassing oxidative damage and structural alterations. Despite a growing need for effective interventions, the existing therapeutic repertoire for treating skin photoaging remains constrained. Recent investigations have shifted focus towards the application of hydrogels as a novel avenue for addressing this concern. Various active substances can be combined with hydrogels for transdermal delivery, including compounds from the ocean, plants, cell active substances, which can promote skin UV damage repair mainly through antioxidant, anti-inflammatory and promote collagen production. This review seeks to offer a thorough summary of recent progress in employing hydrogels for addressing skin photoaging. Topics covered include the mechanism of skin photoaging, and emerging trends in hydrogel-based therapies for skin rejuvenation. The discussion also explores challenges and outlines potential future directions in leveraging hydrogels as therapeutic agents to address skin photoaging.